SPECTROSCOPIC ANALYSIS OF THE PROCESS OF COMPLEX FORMATION OF ALUMINUM ION WITH OXYAZOREAGENTS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In recent years, we can observe an increase in environmental pollution, that is, poisoning of the environment with various heavy and toxic metals. The reason for this is the increase in anthropogenic influence, that is, the increase in production and industry. Among the main national threats that threaten the ecological security of our country, it is necessary to highlight the pollution of water resources, natural and man-made disasters, production and household waste, radiation pollution of some areas and groundwater pollution[1-3].